School Readiness for Young Migrant Children: The Challenge and the Outlook. (5th March 2012) - Mathur, Smita; Parameswaran, Gowri
Abstract : There is evidence that children from families of migrant workers are among the most disadvantaged in term of early academic achievement. Yet there are insufficient resources allocated to research exploring the reasons that existing preschool programs are not effective in closing the gap between migrant children and other groups of children in the USA. There are some Head Start programs that migrant children have access to, but many of them offer simply care-giving functions and offer little opportunities for enrichment activities for children in preschool. This paper explores some of the barriers to engaging the preschool child effectively in educational activities.